Does small-sided-games’ court area inﬂuence metabolic, perceptual, and physical performance parameters of young elite basketball players? - Marcelino, PR; Aoki, MS; Arruda, AFS; Freitas, CG; Mendez-Villanueva, A; Moreira, A (Biology of Sport, 2016)
The purpose of this study was to investigate the effect of court size on physiological responses and physical performance of young elite basketball players. Twelve male basketball players (18.6 ± 0.5 years; 88.8 ± 14.5 kg; 192.6 ± 6.5 cm) from an under-19 team performed two small-sided games (matches) with different court areas (28x15 m and 28x9 m; 28x15 and 28x9 protocols). The number of players (3x3) was kept the same in each protocol. The players performed a repeated-sprint ability (RSA) test before and after each match. Blood lactate concentration was collected before (pre) and after (post) the matches, and the session rating of perceived exertion (session-RPE) was determined 30 minutes after the match. Best and mean time in the RSA test were not different between the 28x15 and the 28x9 match protocols (p>0.05). A significant difference was observed for lactate concentration from pre- to post-match (p 0.0S, ES=(0.41). In summary, the results of the current study suggest that the different court areas induced similar responses. Although there was no significant difference in effort perception, players tended to perceive a greater effort in the larger court size.